2005
DOI: 10.1183/09031936.05.00054304
|View full text |Cite
|
Sign up to set email alerts
|

Obesity increases the risk of incident asthma among adults

Abstract: The annual incidence of asthma in adults in northern Sweden has been estimated at 2.3 per thousand population. Risk factors for incident asthma among adults were studied in a case-referent study based on incident cases of asthma during 1995-1999.The healthcare providers reported suspected cases of incident asthma. After clinical examination, 309 (65% female) of 473 reported subjects were included. Inclusion criteria were a history of incident asthma (onset ,12 months) and verified bronchial variability. Refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 29 publications
10
164
2
6
Order By: Relevance
“…Suboptimal treatment outcomes in patients with risk factors for poor asthma control have been suggested to be associated with insuf ficient drug deposition in the small airways. 32,33 It is important because the small airways seem to be particularly affected both in smoking and obese asthmatics. Apart from the disturbances in ventilatory function of the lungs in this group of patients, the tendency of the small airways to clo sure has been also emphasized.…”
Section: Resultsmentioning
confidence: 99%
“…Suboptimal treatment outcomes in patients with risk factors for poor asthma control have been suggested to be associated with insuf ficient drug deposition in the small airways. 32,33 It is important because the small airways seem to be particularly affected both in smoking and obese asthmatics. Apart from the disturbances in ventilatory function of the lungs in this group of patients, the tendency of the small airways to clo sure has been also emphasized.…”
Section: Resultsmentioning
confidence: 99%
“…Two other population studies have also shown that obesity is a risk for the combination of symptoms plus AHR. 36,37 Up to 15% of the adult population have asymptomatic AHR, 38 representing a substantial population potentially at risk of developing symptoms in the presence of obesity.…”
Section: Perception Of Dyspneamentioning
confidence: 99%
“…A clear explanation for the rising rates and associated risks of pediatric asthma and obesity remains elusive. Numerous studies have reported an association between asthma and obesity in adult and pediatric cohorts (16)(17)(18)(19). Sex differences, with stronger associations documented among women, have been observed, although not consistently (16,17).…”
Section: Introductionmentioning
confidence: 97%